Nurses' experiences during the COVID-19 pandemic in Duhok City - Ronak Muhammad Barwari; Sarah Jawad Kadhim; Khalid Ibrahim Mohammed-Saber (Hawler Medical University, 2022)
Background and Objectives: Covid-19 is one of the health issues that has had a major impact on health services all around the world. It was declared a pandemic on March 11, 2021. The nurses were on the frontline of the fight against the Covid-19, which had physical, psychological, social, and economic effects on health and health outcomes. It is crucial that nurses' experiences during the pandemic are identified. This study aimed to explore nurses' experiences, knowledge, and practices regarding the pandemic. Methods: A cross-sectional study was conducted among nurses in the Duhok City in the Kurdistan Region of Iraq. The online survey was distributed to nurses using a structured questionnaire. The number of nurses who participated in the study was 110. The data col-lection was conducted from 10th May to 10th August 2021. Data analysis was conducted using SPSS statistical software (version 23.0). Descriptive statistical analysis was conducted using frequency, percentage, mean, and standard deviation. Results: The study revealed that the mean age of nurses was 30 years with a standard deviation of 7 years. The highest percentage of the nurses (44.5) were a Bachelor's degree holders. The nurses had concerns regarding their employment status, workload, and threatened to leave their job. Having sufficient personal protective devices and work protocols to help decrease the risk of infection and stress and anxiety were important issues. Nurses need more training and support systems from leaders and employers to go for-ward and work safely and comfortably. Conclusions: The study highlighted essential points regarding the nurses' experiences during the pandemic such as the impact of workload, shortage in staffing, threatened termination of employment, and having to do non-nursing activities or tasks. It was clear that the nurse managers have a significant role in providing efficient support to nurses.